Analysis of the RET, GDNF, EDN3, andEDNRB genes in patients with intestinal neuronal dysplasia and Hirschsprung disease. Issue 5 (1st May 2001) - Gath, R; Goessling, A; Keller, K-M; Koletzko, S; Coerdt, W; Müntefering, H; Wirth, S; Hofstra, R M W; Mulligan, L; Eng, C; von Deimling, A
Abstract : BACKGROUND: Hirschsprung disease (HSCR) is a frequent congenital disorder with an incidence of 1 in 5000 live births, characterised by the absence of parasympathetic intramural ganglion cells in the hindgut resulting in intestinal obstruction in neonates and severe constipation in infants and adults. Intestinal neuronal dysplasia (IND) shares clinical features with HSCR but the submucosal parasympathetic plexus is affected. IND has been proposed as one of the most frequent causes of chronic constipation and is often associated with HSCR. METHODS: We examined 29 patients diagnosed with sporadic HSCR, 20 patients with IND, and 12 patients with mixed HSCR/IND for mutations in the coding regions of the RET, GDNF, EDNRB, and EDN3 genes. The entire coding regions were analysed by single strand conformational polymorphism and DNA sequencing. RESULTS: Only three RET mutations were detected in patients with HSCR. In patients with IND or a mixed HSCR/IND phenotype, no mutations in these genes were observed. While HSCR and HSCR/IND showed over representation of a specific RET polymorphism in exon 2, IND exhibited a significantly lower frequency comparable with that of controls. CONCLUSIONS: The mutation frequency found in our sporadic HSCR patients (10%) and the allelic distribution of RET polymorphisms are comparable with earlier published data. A significantly different allelic distribution in an established HSCR associated polymorphism argues against common genetic pathways for HSCR and IND.